Zika transmission patterns: a meta‐review. Issue 5 (1st April 2019) - Runge‐Ranzinger, S.; Morrison, A. C.; Manrique‐Saide, P.; Horstick, O.
Summary: Objective: To assesses what is known and identify knowledge gaps for Zika virus (ZIKV) transmission patterns. Methods: Meta‐review searching the databases BioSys; Cochrane Infectious Diseases Group Specialised Register and Cochrane Central Register of Controlled Trials; EMBASE; Google Scholar; LILACS; MEDLINE (PubMed); Web of Science; and WHOLIS with the term 'ZIKA'. Systematic reviews and reviews specifying the search methods and describing potential modes of transmission were eligible for analysis. Results: Of 5, 401 hits for 'Zika', 44 studies were assessed and 11 included after applying in‐ and exclusion criteria: six systematic reviews and five reviews with specified methods, covering all ways of possible transmission. Results can be grouped into transmission routes with good evidence and agreement between the studies (evidence on vector, mother‐to‐child and sexual transmission) and transmission routes with limited evidence. Transmission by breastfeeding, intrapartum, by animal bites or laboratory‐based remains inconclusive, as these routes are suggested by single studies only. The risk of transfusion transmission is described and public health measures for safe transfusion should be taken as available. Conclusion: Our results imply the need for public health measures to limit transmission via vectors, mother‐to‐child, sexual transmission and blood transfusion. Also needed are long‐term prospective cohort studies covering periods of active Zika virus transmission and measuring epidemiological parameters to establish evidence on other routes of transmission; seroprevalence studies; transmission dynamics modelling and modelling health impacts by different modes of transmission.